Bone Tumor Suppression in Rabbits by Hyperthermia below the Clinical Safety Limit Using Aligned Magnetic Bone Cement (Small 3/2022). Issue 3 (20th January 2022) - Yu, Xiang; Gao, Shan; Wu, Di'an; Li, Zhengrui; Mi, Yan; Yang, Tianyu; Sun, Fan; Wang, Lichen; Liu, Ruoshui; He, Shuli; Ge, Qinggang; Lv, Yang; et al.
Abstract : Bone Tumor Suppression Magnetic bone cement incorporating magnetically soft zinc ferrite nanoparticles and aligned in a direct current magnetic field realized exceptionally high heating power in live animals under clinically safe field parameters for hyperthermia. Suppression of osteosarcoma in rabbits by hyperthermia substantially enhances survival rate. More details can be found in article number 2104626 by Shuli He, Qinggang Ge, Yang Lv, Hao Zeng, and co‐workers.